Kekuatan Hukum Alat Bukti (Novum) Dalam Pemeriksaan Perkara Peninjauan Kembali Beberapa Tindak Pidana Pembunuhan ( Vide Pasal 338 KUHP) - Faradillah Maulidyah Pelu; John Dirk Pasalbessy; Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Novum or new evidence or new circumstances is a condition for submitting a request for review. Review is a legal remedy that can be taken by the convict (the person who is sentenced) in a legal case against a court decision that has permanent legal force in the justice system in Indonesia. Purposes of the Research: Reviewing and explaining the legal strength of the (Novum) evidence in the examination of cases of reviewing several crimes of murder.Methods of the Research: This research uses a normative juridicial research type with a descriptive analitycal type of research. Engineering legal materials by conducting library research on legal materials, namely primary legal materials and secondary legal materials. Legal materials analysis techniques are obtained from qualitative calcifications.Results of the Research: Based on the results of research and discussion, it can be rejected that the submission of a review by the convict/applicant for reconsideration, namely Imam Chambali, is an application that has met the elements of the provisions in Article 263 paragraph (2) of the Criminal Procedure Code and Article 24 of Law Number 48 of 2009 concerning Judicial Power. Novum or new evidence or new circumstances as a basis for filing a petition for review to the Supreme Court.